PENERAPAN TEACHING GAMES FOR UNDERSTANDING UNTUK MENINGKATKAN GERAK DASAR SISWA SD - Alya Dzofira; Taopik Hidayat; Cacih; Meity Suryandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the application of the Teaching Games for Understanding (TGfU) model in improving fundamental movement skills of elementary school students. The problem underlying this research is the low level of students’ basic motor skills due to conventional, teacher-centered learning approaches that lack student engagement and meaningful learning experiences. This study employed a qualitative approach with a library research method by analyzing relevant scientific literature published within the last five years. Data were collected through documentation techniques from books, journal articles, and other academic sources, and analyzed using content analysis methods. The findings indicate that the TGfU model significantly contributes to the improvement of students’ fundamental movement skills, including locomotor, non-locomotor, and manipulative skills. In addition, TGfU enhances students’ tactical understanding, decision-making ability, motivation, and active participation in learning. The game-based learning approach creates an enjoyable and meaningful learning environment, allowing students to actively engage in physical activities. Therefore, TGfU is considered an effective and innovative learning model that can improve not only motor skills but also cognitive, affective, and social aspects of elementary school students.